A Bibliometric Review to Understanding the Supply Chain of Renewable Energy - Mohamud, Ibrahim Hassan; Warsame, Zakarie Abdi (International Journal of Energy Economics and Policy, 2024)
This bibliometric analysis investigates the evolving research landscape in renewable energy supply chains. The study uses VOSviewer software to examine influential articles, authors, countries, journals, and keywords from 2015 to 2023. Notably, 2019 marked a significant shift with a surge in publications and citations, suggesting a transition toward more impactful and higher-quality research. In subsequent years, they have witnessed fluctuations in citation counts, potentially reflecting changes in research focus and publication quality. Geographically, the United States and China stand out as leading contributors, with the United Kingdom, Germany, Italy, and Iran also making substantial contributions. The analysis of journals and publishers reveals variations in research impact and influence, with Elsevier emerging as a significant publisher. The keyword analysis underscores the prevalence of "Supply chains," "renewable energy resources," and "biomass" as central themes. This study offers valuable insights into the research trends and dynamics in the renewable energy supply chain field.